GE_GERICHTE C/21678/2014 vom 16. Oktober 2015 - GE Cour de justice (2015)
PROTECTION DE L'UNION CONJUGALE; DÉCISION D'IRRECEVABILITÉ; MOTIVATION; CONCLUSIONS | CPC.60; CPC.132.1; CPC.318.a; CPC.318.b; CC.28b.1; CC.172.3; CC.175; CC.179.2